Pengaruh Lama Fermentasi dengan Ragi Tape Terhadap Kadar Glukosa pada Umbi Gadung (Disocorea hispida DENNST) - Pagarra, Halifah (bionature, 2010)
This study is an experiment, consisting of two stages. The first stage aims to find a ways of processing umbi gadung (Dioscorea hispida Dennst) against level of  HCN; and second phase aims to determine the effect of fermentation by Ragi tape on the concentration of glucose in umbi gadung. Variable in the first stage of research consisted of two types, namely the independent variables such as processing methods and the dependent variable concentration of cyanide in umbi gadung.  This research using Completely Randomized Design (CRD), consisting of three treatments and one control, comprised of three replications., Namely: Ao: umbi gadung  without treatment (control); A1: umbi gadung  are boiled; A2: umbi gadung  which soaked with salt and A3: umbi gadung  to be smeared with ash wood. The second stage consists of variables, independent variable is the length of fermentation by ragi tape and the dependent variable glucose concentration umbi gadung  flour (Disocorea hispida Dennst). Design used in the study were Completely Randomized Design (CRD), which consists of three treatment groups and one control three repetitions, so there are 12 units of experimental treatments. Each of these treatments are: Po: Flour without fermented umbi gadung  ; P1: umbi gadung  flour is fermented for 72 jam. Test of  glucose concentration with Anthrones yam method. Testing is done in two stages: for 24 hours; P2: umbi gadung  flour is fermented for 48 hours; and P3: umbi gadung  flour fermented first, to determine the effect of umbi gadung  processing methods on the concentration of HCN, to obtain low concentration of tuber and the second HCN: the effect of ragi  tape length of fermentation  of glucose concentration on umbi gadung  low concentration of HCN. Data obtained were analyzed by analysis of variance Fα = 0.05 and followed by LSD α = 0.05. The observation indicates that the first stage of processing methods significantly affected the concentration of HCN, the results of LSD α = 0.05 there is a difference between treatments, and  boiling gives the best results with the average results of HCN concentration: 0%, and the observation of the second phase showed that the effect of length of fermentation by ragi  tape affect glucose concentration, which average at P0: 35.609 ppm; P1: 44.473 ppm; P2: 51.681 ppm; and P3: 91,, 484 ppm. The LSD α = 0.05 there is a difference between treatment and at P3: 72 hours showed the best effect with an average glucose level; 91.48 ppm The LSD α = 0.05 there is a difference between treatment and at P3: 72 hours showed the best effect with an average glucose level; 91.48 ppm. Can be concluded that the best way because it boiling to  decrease HCN concentration on umbi gadung and long fermentation by ragit tape: 72-hour glucose concentration can increase umbi gadung flour